Knowledge and awareness of dental cements among dental students in chennai- A questionnaire survey. - Sneha Harshini S, Dr. Abirami Arthanari (Drugs and Cell Therapies in Hematology, 2021)
Introduction: Dental cements are materials that are set intraorally and that are commonly used to join a tooth and a prosthesis or restoration in a carious tooth. They are commonly used in cementation of prosthesis, restoration, pulpal therapy, obtundent, liners and bases and also in root canal sealers The main objective of the study is to assess the awareness of cements used in dental restorations among dental students. Materials and methods: This study was done among dental students and was conducted through an online survey questionnaire that was circulated among dental students. The responses were collected and statistically analysed through SPSS software version 23.0. Results: This study was conducted among 100 UG dental students. The responses were collected. 56% of the UG dental students know what recent cements used for dental restoration while 44% of them don’t know about any recent discovery. Most of the students have come to know about recent cements and have shown interest towards this study. Conclusion: It can be concluded that the majority of the students are aware of the recent cements used in dental restoration.